Juodosios moters savikūra Gayl Jones romane Evos vyras - Juozapaitytė, Rasa (Literatūra, 2015)
The paper analyses the discourse of the black narrator and protagonist – Eva in Gayl Jones’s novel Eva’s Man. The French feminist theory of l’écriture féminine with its emphasis on textuality of gender has been applied to prove that the Afro-American woman creates her Self while writing and her text becomes the essence of her identity since any other opportunity of emotional, intellectual and spiritual evolution has been denied to her. It is explained that the black woman revolves against the boundaries of the hierarchical system, into which she had been placed, silenced and transformed into an object of male manipulation. The analysis of the novel suggests that the liberation of the black woman from the male construct coincides with the progress of her self-creation. Eva disrupts the rationalistic discourse, subverts the phallologocentric order, and establishes a dialogue of gap and silence. The black narrator’s text transforms the traditional canon of woman as ground, her body as the blank page and subjugates the black male body to secure her ciphers on it as her own text. It has been stressed that the woman’s conscious conversion into the subject and the creator enables her to translate the man into the object.